(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
In this article, the concept of independent employment contract and its fundamentals are an important part of the labor law, as well as the issues related to the calculation of the responsibilities of the parties to each other are analyzed. Specific features of terminating the employment contract with the employee during the period of illness were analyzed based on the experience of foreign countries. In this article, according to Article 165 of the Labor Code (Notice of termination of the employment contract at the initiative of the employer), the period of temporary incapacity for work, as well as the time when he performed state or public duties, is not included in the period of notice to the employee.